2009
DOI: 10.7205/milmed-d-04-6308
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Disease Teleconsultative Support of Deployed Healthcare Providers

Abstract: Specialty teleconsultation is being provided to deployed healthcare providers in the current wars in Iraq and Afghanistan through the use of the Army Knowledge Online (AKO) e-mail service. We reviewed 374 teleconsults received by the infectious disease (ID) service between January 2005 and June 2008. The patients were 65% male, 12% female, 33% the gender was not stated or the consult did not involve an individual, and 41% were U.S. Army. The average response time was under 5 hours. Ninety-one percent of consul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Data from the USA and other NATO countries are more difficult to directly compare, as there is little data published in the same form. A US study on infectious disease telemedicine10 use highlighted MRSA, tuberculosis and leishmaniasis as the top three topic queries, all present in our data. Spanish data11 on evacuations to their Role 4 highlighted few infectious diseases issues.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Data from the USA and other NATO countries are more difficult to directly compare, as there is little data published in the same form. A US study on infectious disease telemedicine10 use highlighted MRSA, tuberculosis and leishmaniasis as the top three topic queries, all present in our data. Spanish data11 on evacuations to their Role 4 highlighted few infectious diseases issues.…”
Section: Discussionmentioning
confidence: 57%
“…The USA has published on data from a worldwide infectious diseases telemedicine service in 2005–2008,10 which showed a broad geographical burden, predominantly from Iraq (60%) and Afghanistan (21%) with MRSA-related (13%) and TB-related (8%) enquiries as the most common. However, this reflects physician use of a telemedicine service rather than the burden of disease.…”
Section: Introductionmentioning
confidence: 99%
“…The US military has successfully used the AKO teleconsultation service in remote locations [3,4,[7][8][9]. Other studies have demonstrated the effectiveness of similar programs for other medical specialties [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Since 2004, the average turnaround time for inquiries via e-mail has been 5 h. During the same period, over 10,000 e-mail teleconsults have been completed, involving several different medical specialties. [13][14][15][16][17][18] About 43% of all consults were in dermatology, followed by infectious disease as a distant second, then by orthopedics and then neurology. Although the total teleconsultation in Iraq made up the vast majority of consult activity up through December 2011, Afghanistan consult activity is expected to surpass Iraq over the next year since the war in Iraq came to a close in December 2011 for U.S. military forces.…”
Section: Telemedicine In Remote Overseas Locationsmentioning
confidence: 99%